ANALISIS PENDAPATAN USAHATANI JAMUR MERANG DAN KONTRIBUSINYA TERHADAP PENDAPATAN RUMAH TANGGA PETANI DI KELURAHAN SEMPUSARI KECAMATAN KALIWATES KABUPATEN JEMBER - Farah Rizqi Fauziah; Djoko Soejono (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2019)
The mushroom farming in Sempusari Village was a subsidiary farm to increase farm household income and it was a diversion commodity from secondary crops. The diversion decided due to there was an opportunity to use the remaining of the house yard. The straw mushroom farmers in this region are still not join any association or farmer groups, so that the farmers do the cultivation independently without any help. This study aims to determine 1) income of straw mushroom farming, 2) production cost efficiency of straw mushroom farming, 3) the contribution of straw mushroom farming profit to the farm household income of farmer households. The research method used descriptive and analytical methods. The sample used total sampling method. Data collection used observation, interview and documentation techniques. Data analysis used income analysis, R/C ratio analysis and income contribution analysis. The results showed that straw mushroom farming in Sempusari subdistricts was profitable, its cost is efficient and the amount contribution of it is rated medium.